Letterpress revolution : the politics of anarchist print culture - Ferguson, Kathy E. (Duke University Press, 2023)
"Anarchist collectives and associations have a long and robust history of independent publications and journals. Letterpress Revolution explores the radical print history of anarchism in the US and England from the late-19th century to the present to show how anarchist print culture has thrived through a combination of media technology, epistolary relations, and radical scholarship. Kathy Ferguson tells the story of anarchist presses, often located centrally in the homes, offices, and community centers of anarchist movement and run by everyone from professional union printers laboring in their off hours to lay artists and craftspeople learning new skills. These presses created what Ferguson calls a "fugitive public" that produced anarchist knowledge outside of formal educational institutions. Although anarchists are politically committed to dispersed and independent collectives, Ferguson argues that anarchist print culture has created an assemblage of dynamic and entangled networks that brings the movement together. Finally, Ferguson considers contemporary letterpress printers and other anarchist formations around material and intersectional politics that continue today-including Food Not Bombs, Protect Maunakea ʻOhana, and the feminist bookstore movement-which, she argues, strengthens anarchist theory by incorporating thing power and a critical analysis of anti-Blackness into anarchist politics"--